Evaluate the effectiveness of Bait Cobamid Kibamid 7.5 to control cockroaches in urban areas in Hanoi - Ngo Xuan, Nam (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3DO - 10.25073/2588-1140/vnunst.4521, 2017)
Bait Cobamid 7.5 RB was a product that researched on by the Institute of Ecology and works protection.  The aim of this study was to investigate the usage this bait formulation against cockroaches field infested in 18 flats of Hanoi. There results showed that bait Cobamid 7.5 RB was highly effective in field cockroaches infested. Cockroaches eliminated completely from 18 works after 4 weeks and no cockroaches reinfection after 28 weeks of treatment. The average amount of bait to use on a flat range from 12-35 g and average is 24g.